A review on the crystalline silicon bottom cell for monolithic perovskite/silicon tandem solar cells. (August 2019) - Yan, L.L.; Han, C.; Shi, B.; Zhao, Y.; Zhang, X.D.
Abstract: Perovskite/silicon tandem solar cells have reached certified efficiencies of 28% (on 1 cm 2 by Oxford PV) in just about 4 years, mostly driven by the optimized design in the perovskite top cell and crystalline silicon (c-Si) bottom cell. In this review, we focus on the structural adjustment of the bottom cell based on the structural evolution of monolithic perovskite/silicon tandem solar cells to improve their performance. To begin with, c-Si solar cells are classified into silicon homojunction and silicon heterojunction (SHJ) devices according to temperature tolerance, and the corresponding structural features are presented. Then, the evolution of monolithic perovskite/silicon tandem cells based on c-Si homojunction and heterojunction bottom devices is summarized. An appropriate candidate of the c-Si bottom cell for monolithic perovskite/silicon tandem cells is proposed, mainly including passivated emitter and rear cell devices, the tunnel oxide passivated contact cell, and SHJ devices. In brief, our review will emphasize the important role of the c-Si bottom cell with different passivation structures for perovskite/silicon tandem cells, which provides a guidance to enhance the performance of tandem cells.